Application of Taguchi method to analyse the impacts of common process and batch size in multistage production system under uncertain conditions - Wazed, M.A.; Ahmed, S.; Nukman, Y. (2011)
1 to determine the optimum level of batch size in bottleneck facility 2 to analyse the effect of common processes on throughput and cycle time in a multistage production system under machine breakdown and quality uncertainty. In this research, the authors developed simulation models for multistage production system under common processes in an uncertain situation created by machine breakdown and quality variation. Few simulation models are developed based on a live case from a company. The models are verified and validated with the historical data from the company and by face validity. Taguchi approaches for orthogonal array are used in designing experiments. The experimental settings are executed in WITNESS, a simulation package. It is observed that the variation in level of common process in the system has significant impact on the production quantity and cycle time. There is strong interaction among the common process and the batch size in lancing stations. The production quantity is elevated and cycle time is least when the batch size in bottleneck facility is 12 and two common processes are used.